2008
DOI: 10.1086/591966
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Effect of 7‐Valent Pneumococcal Conjugate Vaccine on Pneumococcal Colonization among Unvaccinated Household Members

Abstract: Vaccine-type pneumococcal carriage was lower among adults and unvaccinated children living with a PCV7 vaccinee. This is attributable to reduced exposure and reduced transmission when exposure occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0
8

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 24 publications
(32 reference statements)
4
92
0
8
Order By: Relevance
“…[3][4][5][6] The rate of IPD has also declined among unvaccinated older children and adults. 3,7,8 However, data regarding the effects of PCV7 among infants who are too young to be fully immunized are limited. 9,10 Neonates and young infants are particularly vulnerable to serious bacterial infections, which may result from either vertical or horizontal transmission.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] The rate of IPD has also declined among unvaccinated older children and adults. 3,7,8 However, data regarding the effects of PCV7 among infants who are too young to be fully immunized are limited. 9,10 Neonates and young infants are particularly vulnerable to serious bacterial infections, which may result from either vertical or horizontal transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Carriage of bacterial pathogens is clinically important because in some individuals carriage may be a prelude to invasive infection (4)(5)(6)(7)(8)(9)(10)(11). In contrast, some early studies suggest that GAS carrier strains have reduced ability to cause disease (12)(13)(14).…”
mentioning
confidence: 99%
“…Reports from other countries have indicated that the prevalence of VT pneumococci is individually reduced after PCV7 administration (6,7). Millar et al reported that VT pneumococcal carriage was lower among adults and unvaccinated children living with others who received the PCV7 vaccine (8). In the United States, the decreased nasopharyngeal carriage of VT strains among PCV7-immunized children led to decreased transmission to nonimmunized children and adults (i.e., herd immunity) (4).…”
Section: Discussionmentioning
confidence: 99%